2001
DOI: 10.1161/01.hyp.38.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Clonidine Administration on Sympathetic Nerve Traffic and Baroreflex Function in Heart Failure

Abstract: Abstract-Congestive heart failure is characterized by a sympathetic activation that is coupled with a baroreflex impairment. Whether these alterations are affected by clonidine is unknown. In 26 normotensive patients age 58.0Ϯ1.1 years (meanϮSEM) affected by congestive heart failure (New York Heart Association functional class II or III) and treated with furosemide and enalapril, we measured mean arterial pressure, heart rate, venous plasma norepinephrine, and muscle sympathetic nerve traffic (microneurography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
4
17
2
Order By: Relevance
“…The addition of moxonidine had no influence on baroreceptor sensitivity-that is, the capacity to increase or decrease MSNA or heart rate to buffer short-term BP fluctuations. In that respect, moxonidine does not differ from clonidine, which also does not affect baroreceptor sensitivity, when assessed by identical methodology (22,23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The addition of moxonidine had no influence on baroreceptor sensitivity-that is, the capacity to increase or decrease MSNA or heart rate to buffer short-term BP fluctuations. In that respect, moxonidine does not differ from clonidine, which also does not affect baroreceptor sensitivity, when assessed by identical methodology (22,23).…”
Section: Discussionmentioning
confidence: 92%
“…This finding points to mechanism(s) independent of the renin-angiotensin system in the pathogenesis of sympathetic hyperactivity. Also, in patients with heart failure who receive chronic treatment with an ACE inhibitor or AngII antagonist, MSNA was normalized only after the addition of clonidine (22).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sympatholytic medications acting in the brain, such as clonidine, reduce sympathetic nervous system activity and blood pressure. [25][26][27] The hypothesis that blood pressure reduction is mediated through the central nervous system is further supported by the time course of the response. Normally, blood pressure reduction elicits a baroreflex-mediated increase in heart rate and in circulating renin concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Clonidine, an ␣ 2 and I 1 receptor agonist, has been used for this purpose. Grassi et al 12 have recently reported a 26% reduction in muscle sympathetic burst frequency and a 47% fall in PNE concentrations after 2 months of 0.1 mg clonidine daily, administered by transdermal patch. More selective I 1 agonists, such as rilmenidine and moxonidine, have fewer side effects than clonidine.…”
mentioning
confidence: 98%